Development and Validation of the Greek version of Self-Care Heart Failure Index (Gr-SCHFI) in Patients with Heart Failure - Lambrinou, Ekaterini; Thodi, Maria; Samara, Anastasia; Philippou, Katerina; Paikousis, Lefkios; Sentouxi, Panayiota; Filippatos, Gerasimos; Bistola, Vasiliki; Parissis, John; Kyriakou, Martha (My University, 2022)
Background: Self-care of patients with heart failure (HF) is essential for the effective self-management of their disease, especially during the pandemic era. Self-care assessment instruments give the opportunity to Health Professionals to early recognize possible self-care needs and management of patients with HF. Aim: The translation and validation of the Greek version of the instrument “Self-Care of Heart Failure Index’’ (Gr-SCHFI), as well as the investigation of the psychometric properties of the instrument in a Greek-speaking population with HF. Methods: It’s a methodological study of an instrument validation. The psychometric properties of the Greek version of Gr-SCHFI were evaluated through reliability factors (Cronbach’s a and Composite Reliability), reliability of repeat test-retest and validity measures (content validity and concurrent validity). Brislin's (1970) methodology was used to translate the instrument to Greek language. Results: The study involved 176 patients, of whom 138 (78%) were men with an average of 69 years old. Most participants were in the NYHA III category [76 (57%)]. Confirmatory factor analysis showed very good measurements in the criteria: RMSEA = 0.07, CFI = 0.97, GFI = 0.98, AGFI = 0.98, NFI = 0.95, TLI = 0.97. The Cronbach's alpha index and the Composite reliability index had satisfactory internal coherence indicators (Cronbach's alpha 0.80-0.92, and Composite reliability 0.88-0.96, respectively). Conclusions: The Gr-SCHFI scale is a reliable and valid self-care assessment instrument for patients with HF. Self-care is necessary in HF where the evaluation and assessment of the self-care of the specific population is very important along the trajectory of the disease.
Keywords: Psychometric properties; Self-Care of Heart Failure Index; Heart failure; Self-care; Self-management